Performance of a Single Cylinder Direct Injection 4-Stroke Diesel Engine under Effect of Using Diesel and Naphtha Blends - Basas, Marwah E.; Khalefa, Rafeq A. (Advances in Mechanical and Materials Engineering, 2023)
The demand for diesel fuel in the transport industry is expected to rise due to greenhouse gas laws and global economic expansion, necessitating the search for alternative energy sources. If light distillate fuels can match diesel fuel’s efficiency and cleanliness at a more affordable cost, they could potentially enter the market. The aim of the investigations was to assess a single cylinder, four stroke diesel engine’s performance using various blends of diesel (D) and heavy naphtha (N): D100%, D97.5%N2.5%, D95%N5%, D92.5%N7.5%, and D90%N10%. Tests were conducted at 3000 rpm and variable loads, revealing that the maximum permissible naphtha content in diesel oil (D100%) is 10%. Higher naphtha proportions led to misfire and instability under heavy loads. 100% diesel demonstrated the lowest brake-specific fuel consumption and higher thermal efficiency, while mixture of 90% diesel and 10% naphtha showed the highest fuel consumption and lower thermal efficiency.